Solve.

2x^2/3 - 5x^1/3 = 3

Please show your steps. Thank you!

First, you can say m = x^1/3

2m^2 - 5m = 3

Subtract 3 from both sides

2m^2 - 5m - 3 = 0

Using the x-method or the grouping method:

(2m+1)(m-3) = 0

2m+1= 0 or m-3= 0

solve for m

m = -(1/2) or m= 3

plug x^1/3 in for m

x^1/3 = -(1/2) or x^1/3 = 3

square root to the power of 3 to both

x = -(1/8) or x = 27

Hope this helps!

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up